Spirit Confronts the Four-Headed Monster: Jean-Bertrand Aristide’s Mistik–Infused Flood-Rise in Duvalierist Haiti - Geoffrey Kain (Humanities, 2020)
To explore Jean-Bertrand Aristide’s rise from obscure rural Haiti to become the nation’s first democratically elected president—by a landslide—is to enter into a world and a swirl of events that reads like surreal fiction or magical realism. As a Catholic priest (Salesian order), Aristide was fueled by the religio-socialist principles of liberation theology, which emerged as a significant force in Latin America primarily in the 1970s and 1980s, forcefully and vocally advocating for the masses of Haitian poor mired in deeply-entrenched disenfranchisement and exploitation. As a charismatic spokesperson for the popular democratic movement in Haiti during an era of entrenched dictatorship and repressive violence, Aristide boldly confronted the “four-headed monster” of the Haitian power structure—the army, the church hierarchy, the tontons macoutes, and the wealthy elite. His seemingly impossible escape from multiple assassination attempts, together with the power of his colorful rhetoric and his close association with urban slum dwellers and rural peasants, led to a rising “flood” (or lavalas) that invested him with an aura of Spirit, or mistik, that in either/both the Haitian-embraced tradition of Christianity or vodoun (voodoo) served to energize and greatly reassure an intense mass movement arrayed against seemingly impossible odds. This article focuses on the rise of Aristide as the embodiment and voice of Spirit among the people and does not extend into his tumultuous secular years in and out of the presidency, having been twice the victim of coups (1991 and 2004); instead it focuses primarily on the years 1985–1990 and does not enter into an assessment of Aristide as president. Aristide’s own vivid narratives of this time, segments of his sermons, and later, passages of his poetry serve to bolster the literary quality or interpretation of this brief but vividly colorful historic epoch in the Haitian experience.